Behçet's disease presenting as new onset of confusion in a male patient of North African origin in the UK. (21st December 2010) - Dolan, Ross; Watson, Suzanne; Bathgate, Debbie
Abstract : A 50-year-old right-handed man presented with headache accompanied by new onset confusion and slurring of speech over a 5-day period. This was initially suspected to be due to a transient ischaemic attack. On examination he had a clear ptosis of his left eye, which had developed just 6 days prior to his most recent admission; however, the rest of his neurological examination was normal. A neuropsychiatric review showed poor verbal recall, below average visual contrast ability and below average verbal learning scores. He had a medical history of recurrent oral ulcerations accompanied by anterior uveitus and recurrent genital ulcerations on the scrotum. Imaging showed increased unilateral signal in the left thalamic area, which when taken together with the clinical history, supports the internationally recognised diagnostic criteria for Behçet's disease. The patient lacked insight into his condition meaning that long-term residential care may be required.